TCR-independent CD28-mediated gene expression in peripheral blood lymphocytes from donors chronically infected with HIV-1. - Wong, J G (1997)
Complete activation of peripheral blood T cells requires both T-cell receptor (TCR) stimulation and CD28 costimulation. Signalling pathways associated specifically with CD28 are not well understood, however, because ligation of CD28 in the absence of TCR stimulation does not give rise to cellular responses in normal cells. In peripheral blood lymphocytes (PBL) from donors chronically infected with human immunodeficiency virus-1 (HIV-1), CD28 can induce viral replication through an alternative pathway that does not require TCR ligation. We have exploited this observation to study CD28-mediated signal transduction using reverse transcriptase-mediated polymerase chain reaction (RT-PCR) to amplify viral RNA. Independent ligation of CD28 on donor PBL induced expression of the HIV-1 tat gene but not the interleukin-2 (IL-2) gene. Viral induction did not occur following pretreatment of cells with actinomycin D, suggesting it was mediated through transcriptional activation of the viral long terminal repeat (LTR). tat was induced in the presence of the protein kinase C inhibitor H-7, but was inhibited by cyclosporin A. Our results demonstrate that CD28 is linked directly to specific signalling pathways leading to de novo induction of genes in PBL.